Activation of the E3 ubiquitin ligase Parkin. (7th April 2015) - Caulfield, Thomas R.; Fiesel, Fabienne C.; Springer, Wolfdieter
Abstract : The PINK1 (phosphatase and tensin homologue-induced putative kinase 1)/Parkin-dependent mitochondrial quality control pathway mediates the clearance of damaged organelles, but appears to be disrupted in Parkinson's disease (PD) [Springer and Kahle (2011) Autophagy 7, 266–278]. Upon mitochondrial stress, PINK1 activates the E3 ubiquitin (Ub) ligase Parkin through phosphorylation of the Ub-like (UBL) domain of Parkin and of the small modifier Ub itself at a conserved residue [Sauvé and Gehring (2014) Cell Res. 24, 1025–1026]. Recently resolved partial crystal structures of Parkin showed a 'closed', auto-inhibited conformation, consistent with its notoriously weak enzymatic activity at steady state [Wauer and Komander (2013) EMBO J. 32, 2099–2112; Riley et al. (2013) Nat. Commun. 4, 1982; Trempe et al. (2013) Science 340, 1451–1455; Spratt et al. (2013) Nat. Commun. 4, 1983]. It has thus become clear that Parkin must undergo major structural rearrangements in order to unleash its catalytic functions. Recent published findings derived from X-ray structures and molecular modelling present a complete structural model of human Parkin at an all-atom resolution [Caulfield et al. (2014) PLoS Comput. Biol. 10, e1003935]. The results of the combined in silico simulations-based and experimental assay-based study indicates that PINK1-dependent Ser 65 phosphorylation of Parkin is required for its activation and triggering of 'opening' conformations. Indeed, the obtained structures showed a sequential release of Parkin's intertwined domains and allowed docking of an Ub-charged E2 coenzyme, which could enable its enzymatic activity. In addition, using cell-based screening, select E2 enzymes that redundantly, cooperatively or antagonistically regulate Parkin's activation and/or enzymatic functions at different stages of the mitochondrial autophagy (mitophagy) process were identified [Fiesel et al. (2014) J. Cell Sci. 127, 3488–3504]. Other work that aims to pin-point the particular pathogenic dysfunctions of Parkin mis-sense mutations have been recently disseminated (Fabienne C. Fiesel, Thomas R. Caulfield, Elisabeth L. Moussaud-Lamodiere, Daniel F.A.R. Dourado, Kotaro Ogaki, Owen A. Ross, Samuel C. Flores, and Wolfdieter Springer, submitted). Such a structure–function approach provides the basis for the dissection of Parkin's regulation and a targeted drug design to identify small-molecule activators of this neuroprotective E3 Ub ligase.